In Vitro Analysis of Gradual Water Extract of Red Betel Leaf (Piper crocatum) as Free Radical Scavenging and Inhibitor of α-Glucosidase - Safithri, Mega; Fibri Yuniasih, Tiara; Syaefudin (IPB University, 2023)
Red betel (Piper crocatum) has antihyperglycemic activity for diabetic treatment. The purpose of this study was to investigate the activity of DPPH free radical scavenging, the α-glucosidase inhibitory activity, and total phenolics of the aqueous extract of P. crocatum (1st extract, 1st extract residue, and 2nd extract residue). The infundation method was used with spectrophotometric test techniques. The red betel leaves extract in all extracts and extract residues had a small of α-glucosidase inhibition activity ranging from 0.76% - 1.43%. Meanwhile, the antioxidant activity of DPPH and total phenolic levels showed significantly different results (p<0.05) in the 1st extract, 1st extract residue, and 2nd extract residue. The highest antioxidant capacity and total phenolic content were found in the first extract, it were 59.64 ± 0.18 mg AAE/g extract and 55.50 ± 0.14 mg GAE/g, respectively. Gradual extraction reduced DPPH free radical scavenging activity, α-glucosidase inhibition activity and phenolic total content.